Consumer preferences for pork chops in five Canadian provinces. (July 2017) - Ngapo, T.M.
Abstract: The aim of this study is to identify the most important characteristics of fresh pork that determine consumer choice in five Canadian provinces. Within-consumer preference replication and systematic image manipulation in surveying showed differences in strategies for pork choice in lean colour (P < 0.001) and marbling (P = 0.006). High proportions of Nova Scotians (29%) chose light red pork, Albertans (42%) dark red and Quebecers (29%) non-marbled pork. Overall, the most important choice criteria were fat cover (57% preferred lean, 8% fatty) and lean colour (35% dark red, 18% light red). Marbling and drip were less used, but are important noting that 26% of consumers used three or four characteristics to make their choice. The preferences are readily met by the industry, but unfortunately, preferences for minimal or no marbling and fat cover likely result in a compromised gustative experience for many Canadian consumers.